SELEKSI GALUR KEDELAI (Glycine max (L.) - Siti Aminah; Rosmayati Rosmayati; Luthfi A Mahmud Siregar (Universitas Sumatera Utara, 2013)
Strain Selection of Soybean ( Glycine max (L) Merril) of F3 Generation on Saline Soil. Salinity isone of the most serious and widespread agricultural problems resulting in losses of yield. Generally,as land is more intensively cultivated, the salinity problem becomes more severe. A highconcentration of NaCl greatly reduces growth of both the shoot and the root. One strategy availableto cope with saline soil is to choose salt-tolerance crops or to select salt-tolerance cultivars within acrop. This research aims to select the soybean that can grow and has a higher production on salinesoil of F3 generation. This research was conducted in the experiment area at Desa Tanjung Rejo,subdistrict of Percut Sei Tuan, Regenecy of Deli Serdang in the elevation of 1.5 m on above sealevel since Apryl 2012 up to Juny 2012. The experiment design applied in this research is a crosssection analysis that consist of 1 variety, and the applied methot is a F3 generation pedigreeselection, the population is sample, the number of live plant is 137 of 2118. The selected plant isbased on the grain production per plant for 39 plants. Based on the results of research indicates thatbased on the highest weight of seed per plant is 4.9 g on the plant number 1305.2.20 and the lowestproduction is 0.2 g on the plant number 88.5.10 and 88.5.11. The component of production that hasa direct influence to the grain production per plant is the number of branch, age of flowering,number of pod and number of pods contain. Component of production that giving the highest directinfluence is the number of pod contain for 0.832.Keywords : species, soybean, selection, saline soil.